2014
DOI: 10.5301/jva.5000305
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Outcomes in Native AV Forearm Radio-cephalic Fistulae; the CAVeA2T2 Scoring System

Abstract: The CAVeA2T2 scoring system is a potential scoring system for predicting fistula patency rates and the likelihood of dialysing through a fistula. Further studies and/or external validation is required in the context of methodological limitations. How to manage patients with a high CAVeA2T2 score is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…However, the survival time evaluated by these models was not longer than two years. [16][17][18] Given that the median survival of AVFs was approximately 3.2 years, 7) a prediction model that can forecast AVF survival for a longer duration would be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…However, the survival time evaluated by these models was not longer than two years. [16][17][18] Given that the median survival of AVFs was approximately 3.2 years, 7) a prediction model that can forecast AVF survival for a longer duration would be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…(10,11,12,13) This is a typical problem in studies of vascular access as 9 different and often non-standardized outcomes are commonly described in different studies making comparison challenging and recommendations for standard outcome measures is mandated. (17) The number of patients involved in the modelling process in the identified studies (n=218 to 422) compares poorly to available models on other topics such as end stage renal failure where numerous models used over 5000 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Three models used multivariable regression model whilst the other two models used a series of separate univariable cox regression analyses. All studies clearly identified the type of statistical method that they used to derive the prediction model, two were derived using a Cox proportional hazards model (12,13) and three models used logistic regression (10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, few studies have incorporated the clinical features of patients into a prediction model for AVF nonmaturation or AVF failure after creation [1415161718]. Additionally, no study has developed a scoring system to predict the survival of AVF after maturation.…”
Section: Introductionmentioning
confidence: 99%